Adoption of Cashless Economy: A Review - Zargar, Nasir Ahmad; Handoyo, Rossanto Dwi; Heiqbaldi, Unggul; Ibrahim, Kabiru Hannafi; Ali, Umar; Ula, Erika Nafatul (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
The adoption of cashless economies has become a popular trend globally. Cashless transactions provide convenience, security, and faster processing times compared to traditional cash payments. This review intends to provide an overview of the adopted literature on cashless economies, including their drivers and barriers. The review highlights the role of technology, government policies, and social factors in shaping the adoption of cashless economies. Additionally, the review discusses the implications of the adoption of cashless economies for businesses and consumers, including potential risks such as cybersecurity threats and the exclusion of individuals without access to digital payment systems. The review concludes with recommendations for stakeholders in promoting the adoption of cashless economies while addressing the challenges associated with this transition. Overall, this review provides valuable insights into the current state of the adoption of cashless economies and the factors that influence it.